Identifying Patterns of Comorbidities with Cancers of the Colon and Rectum, as Related to age at Diagnosis - Gheybi, Kazzem; Roder, David; Buckley, Elizabeth; Virty, Agnes (International Journal of Population Data Science, 2020)
Introduction Australians have a high incidence of Colorectal cancer (CRC) and it is the second leading cause of cancer death. CRC patients experience more comorbid conditions such as diabetes and heart diseases than expected from population norms. It is anticipated that older patients with CRC will have even more comorbidities. Approach Data from South Australia Cancer Registry were linked with hospital inpatient separations (public and private) and Pharmaceutical Benefit Scheme data to acquire a detailed dataset of CRC patients in South Australia. We have investigated the prevalence of different comorbidities by age and subsite (colon vs rectal) in the 12 months period prior to CRC diagnosis using the chronic comorbid conditions used by Charlson and RX-risk indices. Results Of 11,656 CRCs diagnosed in 2003-2013, a significant higher prevalence of comorbidity presented in colon than rectal cancer patients using either indices. The most prevalent comorbidities for colon and rectal cancers respectively were: hypertension (25.9%, 22.0%), diabetes (17.3%, 15.6%) and gastric disease (11.4%, 12.4%). Common medications for colon and rectal cancers respectively were: hyperlipidaemia (38.4%, 33.7%), hypertension (38.0%, 31.7%) and gastroesophageal reflux diseases (36.2%, 26.8%). In younger patients (<50 years) with colon and rectal cancer anaemia (9.1%) and diabetes (7.4%) were the most prevalent comorbidities and gastroesophageal reflux medications (17.1%) and opioids (14.5%) were used most frequently whereas, in older patients (>79 years) hypertension (36.7%, 32.7%) was the most prevalent comorbid condition and hypertensive drugs (52.23%, 51,72%)were the most frequently used medication respectively. Conclusion Although often regarded as a single disease (CRC), colon and rectal cancers have different predisposing factors and clinical features. As expected, older patients have a higher prevalence of comorbid chronic diseases. We observe, however, that colon and rectal cancer have different comorbidity patterns by age.